Navigating the ethical maze through design action research. Issue 5 (2014) - ,; ,; ,
Abstract : Purpose – The purpose of this study is to identify how ethical stances can be used to develop a frame set in the design of a web‐based decision support system (DSS) for ethical decision‐making and to test both the efficacy of these frames and the potential of such a tool for individuals and groups in both leadership development situations and organisational practice. Unethical behaviour by executives is a frequently cited reason for erosion of trust with other stakeholders.Design/methodology/approach – Utilising action research, by choosing ethics frames such as heuristics, a web‐based ethics DSS designed to enable users to explore ethical issues from multiple perspectives was constructed and this was beta‐tested with a major UK bank and a global oil company.Findings – In orchestrating constant revisions of the ethics frames in the tool, learning from each research cycle was identified, a new form of action research, a design action research, which emphasises the importance of collaboration in the design of such decision‐making tools, was offered and the tool for management development and other applications was successfully beta‐tested.Originality/value – It was demonstrated to management developers how web‐based systems might be designed by non‐information technology professionals; the framing literature was added by demonstrating the value of engaging in dialogue about ethical issues of concern to managers and their organisations and thus improving decision‐making; and additions were made to the literature on ethics and Information systems (IS) and contribution toward action research in the fields of IS and ethics was done. Acknowledgements : The authors would like to extend grateful thanks to the editor and two anonymous reviewers whose advice enabled them to critically review early editions of the paper.